Revitalisasi KUD Untuk Penguatan Lembaga Sosial Ekonomi Di Pedesaan - Masyhuri Mulyono (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2010)
According to UUD 1945, business organization should be developed in the economy is cooperative. KUD (Koperasi Unit Desa = Village Unit Cooperative) is the only developed cooperative, dominant, and widespread all over the country in Indonesia during the New Regime. Since the reformed order, cooperative has been liberalized so many cooperative exist. Finally KUD which was originally developed into the only strong cooperative in the rural area, become undedeveloped one. Beisde , other cooperatives did not developed as well.Without existing strong cooperative, the farmer instituion become weak, their welfare is not increased. How to developed a strong instituion in the rural area, need suitable solution. Actaully although KUD has some weakness, it has many advantages and potential. Therefore KUD revitalization is compose of 5 items : !) community development policy that is pro to KUD, 2) organization business KUD reform, 3) strengthened human resources at KUD, 4) develope cooperation, 5) building image of KUD.